Giant Exchange‐Bias in Polyol‐Made CoFe2O4‐CoO Core–Shell Like Nanoparticles. (23rd August 2018) - Flores‐Martinez, Nancy; Franceschin, Giulia; Gaudisson, Thomas; Beaunier, Patricia; Yaacoub, Nader; Grenèche, Jean‐Marc; Valenzuela, Raul; Ammar, Souad
Abstract: Cobalt ferrite ferrimagnetic nanoparticles (NPs) are prepared and used in this work as seeds to grow a thin antiferromagnetic poly‐ and nanocrystalline CoO shell. The major purpose is to study systematically the characteristics of the as‐produced powders, making emphasis on their internal crystallographic arrangement and their magnetic properties. 57 Fe Mössbauer spectrometry evidences an evolution of the cation distribution among the spinel lattice in the cobalt ferrite core during the core–shell NPs processing. High‐resolution transmission electron microscopy shows a perfect epitaxy between the face‐centered cubic lattices of the spinel core and the rock‐salt shell. Finally, the measurements of 7T‐field‐cooled magnetic hysteresis loops at low temperature (5 K) of the composite particles exhibit a strong exchange bias coupling with an exchange field, µ0 HE, of 365 mT and an enhanced coercive field, µ0 HC, of 1395 mT. These values are very high compared to those of differently prepared CoO‐based oxide composite NPs and for which a giant exchange‐bias is reported. These features are attributed to the favorable material processing conditions offered by the polyol process in terms of crystalline quality, particularly at the interfaces, and for the pinning action exerted by the CoO phase on the magnetization of the CoFe2 O4 phase. Abstract : Oxide‐based core–shell like nanoparticles are produced by the polyol process. Their advanced structural and microstructural characterization highlighted their very exceptional crystallographic quality, making them able to exhibit giant EB feature.